The Influence of Internal Accountability and Financial Transparency on the Efficiency of Regional Government Expenditure - Chalisto, Yohanes; Julianto, Grisologus (Universitas Sains dan Teknologi Komputer, 2025)
Efficiency in public expenditure remains a major challenge in Indonesia's regional financial management, particularly amid fiscal constraints and growing demands for transparency. This study is purposed to examine the influence of internal accountability and financial transparency on the efficiency of regional government expenditure. This research uses secondary data from the Regional Government Financial Reports (LKPD) published by the Directorate General of Fiscal Balance (DJPK) and the Central Bureau of Statistics (BPS), with panel data comprising 34 provinces in Indonesia for the period 2019–2023, and employs a fixed-effects model. The results show that internal accountability and financial transparency both have a positive, significant effect on regional expenditure efficiency. A one-point increase in internal accountability raises efficiency by 0.42 points, while a one-point increase in financial transparency raises it by 0.35 points. These findings imply that a combination of strong internal controls and public financial disclosure fosters fiscal discipline and reduces budget inefficiency. In theoretical terms, this study extends the application of agency theory and new public management in developing economies by highlighting the critical role of the synergy between accountability and transparency in determining sustainable fiscal efficiency in local governance.